In vitro antioxidant anti inflammatory and cytotoxicity activities from Hexane extract of Bryonopsis laciniosa fruits. - Sanjeevkumar C.B; Ramesh L Londonkar; Umesh Madire Kattegouda (International Journal of Phytomedicine, 2018)
Bryonopsis laciniosa also known as “Shivlingi” annual climber with bright red fruits and is reported to be highly medicinal in India. As a folk medicine, the plant is used in treatment of broad range of diseases and disorders. In the present study, Hexane extract of B. laciniosa fruits were used to evaluate in vitro anti inflammatory, antioxidant and Cytotoxicity (towards MCF-7 cell line) activities. In vitro anti inflammatory activity by inhibition of protein denaturation, antioxidant assays like DPPH, ABTS, H2O2 and FRAP were used to measure the antioxidant capacity of the hexane extracts and cytotoxicity activity using MCF-7 breast cancer cell line. Hexane extract showed the effective antioxidant activity in all assays compared to ascorbic acid and BHT. The results for In vitro anti inflammatory activity of hexane extract and Dichlofenac drug were equivalent, hexane extract showed promising activity for inhibition of protein denaturation assay. The cytotoxicity activity from hexane extract was noticeable against MCF-7 cell line. The overall results show potential application of Bryonopsis laciniosa fruits suggesting their potential application as a health-promoting functional ingredient or natural preservative in foods.